2019
DOI: 10.1111/soin.12269
|View full text |Cite
|
Sign up to set email alerts
|

The Kids Are All White: Examining Race and Representation in News Media Coverage of Opioid Overdose Deaths in Canada

Abstract: Problematic opioid use in Canada is on the rise, and opioid overdose deaths now number in the thousands each year. While opioids have long been responsible for overdoses among certain demographics of Canadians, such as drug users on Vancouver's notoriously impoverished downtown Eastside, it is only recently that fatal overdoses have also claimed the lives of White, middle‐class young people. This critical discourse analysis of Canadian news media examines the differences in racial representation in recent cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Analyses of Canadian newsprint media, for example, found that reporting on opioids was dichotomous, featuring patients innocently following physician prescriptions or living lives characterized by addiction and street crime (Webster et al, 2020). While the authors identified date of publication as an indicator for this bifurcation in reporting, other studies of Canadian newspapers demonstrate that race is predictive of how opioid use is characterized (Johnston, 2020). Given these findings, we hypothesized the LS and the ET would describe opioid use, addiction, and overdose through dual lenses of sympathy and criminality, differing in relation to race.…”
Section: Literature: Framing Space Race and Crime In Small Citiesmentioning
confidence: 99%
“…Analyses of Canadian newsprint media, for example, found that reporting on opioids was dichotomous, featuring patients innocently following physician prescriptions or living lives characterized by addiction and street crime (Webster et al, 2020). While the authors identified date of publication as an indicator for this bifurcation in reporting, other studies of Canadian newspapers demonstrate that race is predictive of how opioid use is characterized (Johnston, 2020). Given these findings, we hypothesized the LS and the ET would describe opioid use, addiction, and overdose through dual lenses of sympathy and criminality, differing in relation to race.…”
Section: Literature: Framing Space Race and Crime In Small Citiesmentioning
confidence: 99%
“…I not only contribute to the epistemology of journalism literature, but I also contribute to the journalism studies literature because I explain empirical findings in journalism studies such as that whites are overrepresented in news reports as victims of crimes and police and, on the other hand, that Latinx folks and black folks are overrepresented as criminals (Dixon and Linz 2000; Dixon and Williams 2015; Dixon 2017; Johnston 2019). Journalism studies scholars have also noted that some news organizations that have increased the diversity of their journalist staff members have not proportionately increased the diversity of the information that they report (Benson 2005; Sylvie 2011) even though news staff diversity has been shown to affect journalistic practices and the information they report to some degree (Everbach 2006; Zeldes et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…I take up some of this slack because I evaluate news organizations in terms of their propensity to cause subjects to be in good epistemic states such as justified belief. As a result, this paper is a contribution to the epistemology of journalism literature.I not only contribute to the epistemology of journalism literature, but I also contribute to the journalism studies literature because I explain empirical findings in journalism studies such as that whites are overrepresented in news reports as victims of crimes and police and, on the other hand, that Latinx folks and black folks are overrepresented as criminals (Dixon, 2017;Dixon & Linz, 2000;Dixon & Williams, 2015;Johnston, 2019). Journalism studies scholars have also noted that some news organizations that have increased the diversity of their journalist staff members have not…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Media rarely break from their routines and often cover news from the perspective of the dominant group (Bjornstrom et al, 2010; Marchi, 2008). For example, one analysis found, when studying the opioid crisis in Canada, though there were more indigenous victims than White victims, stories on White victims outnumbered stories on indigenous victims almost 30 to 1 (Johnston, 2019). In the United States, stories about African Americans are often negative, with one account finding that nationwide, local news present a whitewashed image of America in which African Americans interrupt to cause problems or interrupt when they are in need of help (Entman & Rojecki, 2000).…”
mentioning
confidence: 99%